SEROLOGICAL CHARACTERISTICS AND ANTIMOCROBIAL RESISTANCE OF SALMONELLA ISOLATES, RECOVERED FROM ANIMAL RAW MATERIAL - S. Ye. Shmaykhel; N. B. Shadrova; Ye. S. Yerofeyeva; S. I. Danilchenko (Ветеринария сегодня)
Salmonella continues to be the primary cause of foodborne intestinal infections in many countries around the world. According to the offi cial data, 47% of the infection outbreaks in the world are associated with salmonellosis, while chicken meat (34%) plays a signifi cant role in the infection transmission to humans through food. Since the early 90’s of the last century, with the massive use of antibiotics, Salmonella strains resistant to a number of antimicrobials began to appear and currently pose a serious public health problem. Resistant strains persistent in animals can be transmitted to humans through the food chain. The paper presents results of studies of morphological, biochemical, serological properties of Salmonella bacteria recovered from animal raw material: beef, pork, poultry meat, tallow, off al derived from broiler chickens and pig slaughter products. In 2018 the FGBI “ARRIAH” Microbiological Laboratory performed 1,204 tests of animal raw material for Salmonella bacteria and recovered 45 Salmonella isolates. Salmonella bacteria were isolated in accordance with GOST 31659-2012 (ISO 6579:2002). Most Salmonella isolates (56%) were recovered from poultry meat. Biological properties of all the studied isolates were quite typical: they formed hydrogen sulfi de, fermented glucose and mannitol with the formation of gas and acid, did not utilize sucrose, lactose and urea; reaction to indole was negative. It was established that the recovered Salmonella isolates belong to serogroups O7, O9, O5, O4. The frequency of recovering Salmonella group B was 8.9%, group C – 51.1%, group D – 40.0%. Among Salmonella group B, S. derby (4.4%) and S. typhimurium (2.2%) were more common; group C – S. infantis (29.0%), S. virchow (17.8%); group D – S. enteritidis (40.0%). Isolated cases of S. reading (2.2%) and S. oranienburg (4.4%) were observed. All Salmonella isolates recovered from raw material of animal origin demonstrated sensitivity to ciprofl oxacin, chloramphenicol, amoxicillin, amikacin, azithromycin, meropenem, gentamicin, ceftriaxone, kanamycin; were less sensitive to cefotaxime, ampicillin, levofl oxacin and had low sensitivity to nalidixic acid, doxycycline, streptomycin, tetracycline. The phenomenon of multiresistance is characteristic of 44.4% of the isolated Salmonella isolates.